Gynecologic outflow tract obstruction - Pre-operative evaluation and surgical management - Megan T. Vu; Marc A. Levitt; Brent Adler; Devin R. Halleran; Hira Ahmad; Richard J. Wood; Geri Hewitt; Kate McCracken (Elsevier, 2020)
Background: Approximately 7% of adolescent girls have reproductive tract anomalies. Anomalies associated with complete outflow track obstruction present with primary amenorrhea and cyclic abdominal pain. Some outflow tract obstructions may be associated with renal, anorectal, vertebral, cardiac, tracheoesophageal, and limb anomalies. Outflow tract obstructions may occur at varying anatomic locations - vaginal, cervical, or uterine, each requiring different surgical management. Methods: We present the preoperative evaluation and surgical management of three different gynecologic outflow tract obstructions. Results: Physical exam, ultrasound, and MRI were obtained for each patient. The first obstruction was a transverse vaginal septum, which was treated with transperineal resection to allow menstrual egress. The second obstruction was identified as distal vaginal atresia and managed with operative pull-through of her native vagina. The third obstruction was found to be cervico-vaginal atresia and required hysterectomy and salpingectomy with preservation of the ovaries. Conclusions: Preoperative examination of the perineum and imaging with accurate interpretation is crucial to identify subtle but important distinctions in diagnosis, which can result in markedly different interventions ranging from transperineal resection of a transverse vaginal septum, vaginal pull-through procedure, to hysterectomy. The location of the gynecologic outflow obstruction dictates the proper surgical treatment of these patients. Keywords: Mullerian obstruction, Adolescent, Anorectal malformation